2014
DOI: 10.1111/gcb.12467
|View full text |Cite
|
Sign up to set email alerts
|

From projected species distribution to food‐web structure under climate change

Abstract: Climate change is inducing deep modifications in species geographic ranges worldwide. However, the consequences of such changes on community structure are still poorly understood, particularly the impacts on food-web properties. Here, we propose a new framework, coupling species distribution and trophic models, to predict climate change impacts on food-web structure across the Mediterranean Sea. Sea surface temperature was used to determine the fish climate niches and their future distributions. Body size was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 71 publications
2
117
0
Order By: Relevance
“…Recently, the exploration of the plankton "interactome" (Lima-Mendez et al, 2015) allowed to describe how biotic interactions occur across trophic levels and relate to environmental conditions and ecosystem functioning, with many new symbiotic interactions identified (Guidi et al, 2016). When prior knowledge is too limited, food-web models could be inferred from simple size-based, or multi-traits assumptions (Albouy et al, 2014), or based on ecosystem models (e.g., Follows et al, 2007;Le Quéré et al, 2016) in combination with satellite estimates of (phyto)plankton community composition (e.g., Hirata et al, 2011).…”
Section: Species Distribution Modeling-running Before We Can Walk?mentioning
confidence: 99%
“…Recently, the exploration of the plankton "interactome" (Lima-Mendez et al, 2015) allowed to describe how biotic interactions occur across trophic levels and relate to environmental conditions and ecosystem functioning, with many new symbiotic interactions identified (Guidi et al, 2016). When prior knowledge is too limited, food-web models could be inferred from simple size-based, or multi-traits assumptions (Albouy et al, 2014), or based on ecosystem models (e.g., Follows et al, 2007;Le Quéré et al, 2016) in combination with satellite estimates of (phyto)plankton community composition (e.g., Hirata et al, 2011).…”
Section: Species Distribution Modeling-running Before We Can Walk?mentioning
confidence: 99%
“…Thus, to actually change the body-size structure of food webs, warming must have a differential effect on predator and prey size, with predators becoming smaller at a faster pace than their prey. There is yet to be any experimental evidence suggesting that this can happen in nature, although this pattern can be obtained through a differential effect of warming in predator and prey mobility [1], which has been in turn shown to greatly affect food web network structure [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The link between temperature and body-size structure might be related to species identity across habitats, to differences in the way prey selection occurs between species of different habitats [3] or to range shifts with temperature [1,26]. Finally, it can also be due to body size changes of species occurring in different habitats due to differences in environmental temperatures [14,16,24].…”
Section: Discussionmentioning
confidence: 99%
“…As different species and groups have differential responses to warming, effects are seen at every trophic level and can also be amplified up the food chain (Pinsky et al, 2013;Chust et al, 2014). Changes in phenology are not synchronous among phyla and can cause predator-prey mismatches (Arula et al, 2014;Behrenfeld, 2014;Lewandowska et al, 2014), changes to species compositions (Albouy et al, 2014), alterations in food web body size (Gibert and Delong, 2014) and changes in food web composition (Verges et al, 2014). Recent work has suggested that this maybe most pronounced in systems governed by seasonal blooms (Behrenfeld, 2014).…”
Section: Updates To Ar5mentioning
confidence: 99%